PENGARUH EKSTRAK RIMPANG JERINGAU (Acorus calamus L.) TERHADAP MORTALITAS ULAT GRAYAK Spodoptera litura F. - Hasnah Hasnah; Husni Husni; Ade Fardhisa (Jurnal Floratek, 2012)
The purpose of this study was to obtain an effective concentration of the extract of sweet flag rhizome in controlling S. litura. This research was conducted at Laboratory of Plant Pests and Diseases, Agriculture Faculty, Syiah Kuala University, Banda Aceh. This research used a Completely Randomized Design (CRD) non-factorial, with six levels of extract concentrations, that is 0%, 3%, 6%, 9%, 12%, and 15%. Each treatment was repeated four times. The variables measured were mortality of larvae, percentage of formed pupae, percentage of emerging imago, and life length of imago. The results showed that application of the sweet flag rhizome extract affected mortality of larvae, formed pupae, emerging imago, and life length of imago S. litura. Use of sweet flag rhizome extract with a concentration of 3% was effective in controlling S. litura. Application of sweet flag rhizome extract with a concentration of 3% resulted in larval mortality up to 57.50%, formation of pupa only 20%, emerging imago 5%, and average life length of imago S. litura 1.25 days.